Pelatihan Pertolongan Pertama Pada Kecelakaan untuk Guru Sekolah Dasar se-Kecamatan Depok, Sleman, DIY - Yoshima Nekada, Cornelia Dede; Wiyani, Christin (Jurnal Pengabdian Dharma Bakti, 2020)
Accidents might happen anywhere, anytime, and to anyone. Primary school education is a period when children get very active in interacting with other peers. The interaction during a game might cause a risk of injuries on primary school students. Children often ignore the health condition of each other during the interaction. They have yet to own the analytical ability to identify if their friends conceive dangerous diseases, such as congenital heart disease, asthma, or other diseases. Free game interactions among primary school students such as running during the break or physically-related games might increase the risk for accidents or injuries within the school environment. Teachers are the closest people when children are at school. Teachers are demanded to have knowledge and skills in providing the first aid for their students who possibly experience accidents, injuries, or dangerous conditions, such as stopped breathing and cardiac arrest, which might happen during the school hours. The required skills are splinter dressing and/or basic life support. This activity aimed to improve the knowledge and skill of primary school teachers in providing first aid and for them to be capable of performing the basic life support. Coaching and counselling of Basic Life Support as well as splinter dressing were the conducted method. The result acquired from this community service showed that the good level of knowledge before the first aid counselling activity was 19.5%, which increased to 90.2% after the counselling activity. This study concluded that the knowledge of Primary School Teachers in Depok District of Sleman-Yogyakarta regarding First Aid has increased.Keywords: Accidents, Aid, First, Primary, School, Training,